(untitled) (Journal of Engineering, 2008)
Due to the deterioration of water quality within the last few years because of the increase of water consumption and the waste water production and disposal into the river The water quality in both surface and ground water resources was negatively affected .The concept of water quality index is used as a tool for water quality classification in Tigris River within Baghdad City .Twenty two parameters of pollution were selected to measure the water quality indices of Tigris river within Baghdad city .Those parameters were measured during (2000-2004)as average monthly values ,three water treatment plants were selected out of the eight water treatment plants that exist along the river.Al Kharkh water treatment plant to reflect the water quality north of Baghdad ,Al Wathba water treatment plant to reflect water quality at the center and Al Rasheed water treatment plant located south of Baghdad to reflect the water quality at this area .The estimated water quality indices indicated that the river quality deteriorate south of Baghdad and the geological and hydrological conditions played the prime role relative to the agricultural and industrial activities within the catchments on the quality of Tigris river .Furthermore ,due to the continuous decrease of flow and the simultaneous increase in agricultural and industrial development with time ,the river showed a general deterioration in quality while the worst years were 2002,2003 due to the significant decrease in the amount of flow .